2018
DOI: 10.1021/acs.est.8b00711
|View full text |Cite
|
Sign up to set email alerts
|

Linked Response of Aerosol Acidity and Ammonia to SO2 and NOx Emissions Reductions in the United States

Abstract: Large reductions of sulfur and nitrogen oxide emissions in the United States have led to considerable improvements in air quality, though recent analyses in the Southeastern United States have shown little response of aerosol pH to these reductions. This study examines the effects of reduced emissions on the trend of aerosol acidity in fine particulate matter (PM), at a nationwide scale, using ambient concentration data from three monitoring networks-the Ammonia Monitoring Network (AMoN), the Clean Air Status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 79 publications
4
39
0
Order By: Relevance
“…A similar definition has also been applied to the nonrefractory inorganic species measured with an Aerodyne Aerosol Mass Spectrometer (NH + 4 , NO − 3 , SO 2− 4 , and partial Cl − ) (Zhang et al, 2005;Quinn et al, 2006). If the aerosol is near neutral (pH ≈ 7) or acidity is dictated by components other than the inorganic ions in the balance (e.g., organic acids), then charge balance will not provide meaningful information (Trebs et al, 2005;Lawrence and Koutrakis, 1996). Further, the carbonate system (CO 2(aq) -H 2 CO 3 -HCO − 3 -CO 2− 3 ) must be included in the ion balance when the pH is near neutral or higher (Winkler, 1986).…”
Section: Proxies Based On Electroneutralitymentioning
confidence: 99%
“…A similar definition has also been applied to the nonrefractory inorganic species measured with an Aerodyne Aerosol Mass Spectrometer (NH + 4 , NO − 3 , SO 2− 4 , and partial Cl − ) (Zhang et al, 2005;Quinn et al, 2006). If the aerosol is near neutral (pH ≈ 7) or acidity is dictated by components other than the inorganic ions in the balance (e.g., organic acids), then charge balance will not provide meaningful information (Trebs et al, 2005;Lawrence and Koutrakis, 1996). Further, the carbonate system (CO 2(aq) -H 2 CO 3 -HCO − 3 -CO 2− 3 ) must be included in the ion balance when the pH is near neutral or higher (Winkler, 1986).…”
Section: Proxies Based On Electroneutralitymentioning
confidence: 99%
“…Other names have been applied to the DON, including e.g., the neutralization ratio (Lawal et al, 2018). The DON represents the ammonium associated with sulfate + nitrate while DSN represents the ammonium associated only with sulfate.…”
Section: Proxies Based On Electroneutralitymentioning
confidence: 99%
“…Aerosol acidity is among the most important parameters for atmospheric particulate chemistry as it has a large impact on both gas-particle partitioning of semi-volatile ionizable components and rates of many reactions occurring in aerosol liquid water (Seinfeld and Pandis, 2006;Losey et al, 2016;Guo et al, 2017a;Nah et al, 2018;Freedman et al, 2019). Laboratory and field studies have also shown that enhanced acidity in aerosol can increase the formation of secondary organic aerosol (Surratt et al, 2007;Zhang et al, 2007b), one of the major components responsible for particulate air pollution (Zhang et al, 2007a;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies both carried out conceptual modelling or calculations under fixed meteorological parameters. The time series of aerosol pH in six regions within the United States calculated by Lawal et al (2018) showed that pH has seasonal variation that depends on the region, suggesting that changes in meteorological conditions can also contribute to pH changes. Thus, the relative contributions of changes in meteorological conditions and chemical composition to variability in pH are still unclear and require systematic studies.…”
Section: Introductionmentioning
confidence: 99%